Literature Review Human Resources as Strategic Partner of the Organization - Junengsih Junengsih; Martinus Tukiran; Erna Herlina; Muhammad Tito Andrianto; Hermansyah Hermansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The role of employees in the organization is a crucial part to be able to maintain the company and compete with other companies. The reason is, the role of human resources is used as a role within the organization to form a cooperation strategy in order to develop the company for the better. The method used by the researcher is a systematic literature review. The results prove that the role of human resources in the company can be used as a strategic partner for the company, especially when focused on partner organization strategies and the balanced scorecard. So, based on these results, it can be concluded that reliable and quality human resources will make a major contribution to the progress of the organization.